The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.2196/mhealth.4388
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Clinical Decision Support Software by Junior Doctors at a UK Teaching Hospital: Identification and Evaluation of Barriers to Engagement

Abstract: BackgroundClinical decision support (CDS) tools improve clinical diagnostic decision making and patient safety. The availability of CDS to health care professionals has grown in line with the increased prevalence of apps and smart mobile devices. Despite these benefits, patients may have safety concerns about the use of mobile devices around medical equipment.ObjectiveThis research explored the engagement of junior doctors (JDs) with CDS and the perceptions of patients about their use. There were three objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 36 publications
4
37
0
1
Order By: Relevance
“…The authors hope that this paper encourages others to consider undertaking a similar project. The key findings are similar to those reported elsewhere in relation to usefulness as an educational tool at undergraduate level for medical and pharmacy students (16)(17)(18) and to support clinical decision-making in practice (19)(20)(21)(22)(23) .…”
Section: Discussionsupporting
confidence: 87%
“…The authors hope that this paper encourages others to consider undertaking a similar project. The key findings are similar to those reported elsewhere in relation to usefulness as an educational tool at undergraduate level for medical and pharmacy students (16)(17)(18) and to support clinical decision-making in practice (19)(20)(21)(22)(23) .…”
Section: Discussionsupporting
confidence: 87%
“…In the specialty of family medicine (Archibald et al, 2014), residents reported that iPads were valuable when searching for information and for detecting drug interactions but also pointed out that typing notes on a mobile device was not convenient. A study on the use of clinical decision tools in mobile phones revealed an interesting cultural norm of not using mobile devices at patients' bedsides (Patel et al, 2015). However, in the same study, patients were actually positive about doctors using mobile devices in patient care.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the fact that the first prototype of HTE-DLPR is a standalone desktop application which requires prior installation to use and that it lacks automatic data capture have been major factors in the lower assessment of appearance and performance. Both factors are critical factors that can act as limiting barriers in its dissemination in clinical practice [21]. Using QoE tool for mHealth applications may provide major assessment advantages in terms of providing the necessary feedback to users on the detection of potential areas of improvement, the ability to quantitatively assess a mHealth application and to thereby compare it with other similar applications or future versions [17].…”
Section: Discussionmentioning
confidence: 99%